The Correlation Study Between Cytokines Il-6, Tnf- Α And Other Biochemical Parameters With Adipokines Visfatin And Chemerin In End Stage Renal Disease Patients Undergoing Haemodialysis - Mohammed Al Ani, Mohammed Riyadh (2024)
This study aimed to determine the levels of various parameters in patients with ESRD undergoing haemodialysis, to evaluate how dialysis affect these parameters during haemodialysis sessions and to correlate the levels adipokines, inflammatory markers and metabolic parameters in ESRD patients. The study measured serum cytokines (TNF-α, IL-6), serum adipokines (visfatin, chemerin) vitamin D, amylase, glucose, urea, serum lipid profile (cholesterol, HDL, TG), serum liver function test (ALT, AST, ALP, direct bilirubin, total bilirubin, total protein, albumin, LDH) and serum renal function test (uric acid, creatinine, sodium, potassium, chloride, calcium).